Miete or mitte? A preliminary study of vowel length contrasts in Filipino learners of German as a foreign language - Cruz, Frances Antoinette C. (Philippine Journal of Linguistics, 2015)
The present study provides insights into the reception of vowel length in Filipino learners of German. As learning German as an L3 requires phonological awareness of vowel length, an analysis of the relationships between distinguishing vowel length in English, a common L2 in the Philippines, and German, is instructive in determining how L2 competencies and the context of L2 learning influence the acquisition of an L3. Eleven (11) participants took receptive and productive tests to ascertain L2-L3 influences in phonology. In the receptive test, they classified the first stressed vowel in mono- or disyllabic German and English words as long or short. In the second test, the participants recited English and German words containing the target vowels. The recorded vowels, their durations, and long-short ratios were then contrasted with native speakers’ recordings and correlated with variables in a questionnaire on the participant’s linguistic background. The results of the study revealed that exposure to English media had a positive effect on learning German phonology.